UJI AKTIVITAS ANTIINFLAMASI EKSTRAK BATANG AKAR KUNING (Arcangelisia flava (L.) Merr.) SECARA IN VITRO - Syumillah Saepudin; Taufik Septiyan Hidayat; Yunita Al-Azzahra; Ade Cahyati (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Inflammation is a natural response that occurs in tissue damage caused by oxidative stress. Yellow root plant is one of the plants from the Menispermaceae family that contains bioactive compounds with several potential pharmacological activities, including as anti-inflammatory. The purpose of this study was to test the effect of administration of n-hexane, ethyl acetate, and 70% ethanol extract of yellow root on anti-inflammatory activity and test the most optimal anti-inflammatory activity on the type of solvent of yellow root extract (Arcangelisia flava (L.) Merr.). This study used a method of stabilizing red blood cell membranes in vitro which was measured using a UV-Vis spectrophotometer. Stabilization was observed through the inhibitory ability of yellow root extract against red blood cell lysis due to the induction of a hypotonic solution which was then compared with a positive control (Ibuprofen). Results showed that n-hexane, ethyl acetate, and 70% ethanol extracts of yellow root can stabilize red blood cell membranes. Data analysis showed significant significance that there was a significant percent difference in red blood cell membrane stabilization in the four test groups. The most optimal anti-inflammatory activity was found in yellow root n-hexane extract at a concentration of 250 ppm which was 48.76% comparable to the positive control (Ibuprofen) at a concentration of 50 ppm of 59.09%.